Impact of wood fraction, moisture and steam explosion on the development of an innovative insulation material (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The study shows development of an innovative bulk heat insulation material from grey alder (Alnus incana L. Moench) chips and birch (Betula pendula, Betula verrucosa) flakes as residues of plywood production. The research is actual for the plywood production companies and for producers that process grey alder chips to make an innovative products with high added value. Chips and flakes eco-efficient converted to fibrous mass by steam explosion (SE) technology at temperatures (T) of 200 to 235 °C and time interval of 0 to 5 min. Application of SE technology to obtain fibrous insulating material is in the news at a global level and has not been studied previously. The bulk density of raw and SE materials determined using standardised method specified in LVS EN 15103: 2010. The bulk density of SE materials studied depending on the raw material fraction and moisture as well as depending on the SE conditions. The lowest bulk density (53 kg m-3) achieved SE material of grey alder chips with 12% of raw moisture processed at T 235 °C for 1 min. This is the optimal result, which reveals the industrial competitiveness of bulk heat insulation materials and indicate the justification for the further examination.